Performance Of E-Commerce Business - Jessica Jan, Tonga (Universiti Malaysia Sarawak (UNIMAS), 2020)
The study on analysing the performance of e-commerce business is carried out for 10 years from 2008 to 2017 with 8 different companies. This study focuses on microeconomic variables such as profit, which can lead to the performance of the business. The main objective of this study is to analyse the performance of global ecommerce business. Total assets positively affected the financial performance of the e-commerce business globally.